Investigation of structural, optical, and magnetic properties of Nd‐doped Sr2SnO4 Ruddlesden Popper oxide. Issue 10 (23rd June 2020) - Kumar, Upendra; Yadav, Dharmendra; Upadhyay, Shail
Abstract: The samples of Sr2‐x Ndx SnO4 with x = 0, 0.01, 0.02, 0.04, 0.06, and 0.10 were synthesized by a high‐temperature solid‐state ceramic route. Rietveld refining of X‐ray diffraction results showed that all the synthesized compositions are single phase under tetragonal crystal structure. The presence of functional group and local structure has been studied using FTIR and Raman spectroscopy, respectively. XPS study of samples showed the presence of oxygen vacancy and interstitial oxygen in the sample. Optical band gap of samples analyzed by UV‐Vis spectra gradually increases with dopant concentration, and Photoluminescence (PL) spectroscopy study showed most intense emission around 1064 nm. Room‐temperature magnetic hysteresis curve in sample SSN2 showed ferromagnetism, slowly decreasing with Nd and becoming antiferromagnetic for higher compositions. Utilizing the absorption state observed in PL as metastable state makes it promising candidate for laser and IR detector application and the ferromagnetic/antiferromagnetic nature of sample makes it suitable candidate for spintronics device applications. Abstract : Room temperature XRD pattern, crystal structure obtained after refinement, magnetization vs magnetic field curve, and Room temperature absorption spectrum (Tauc plot) for sample SSN2.